Optimized silicon reinforcement of carbon coatings by pulsed laser technique for superior functional biomedical surfaces fabrication. (1st June 2017) - Mihailescu, I N; Bociaga, D; Popescu-Pelin, G; Stan, G E; Duta, L; Socol, G; Chifiriuc, M C; Bleotu, C; Lazar, V; Husanu, M A; Zgura, I; Miculescu, F; et al.
Abstract: We report on the fabrication of silicon-reinforced carbon (C:Si) structures by combinatorial pulsed laser deposition to search for the best design for a new generation of multi-functional coated implants. The synthesized films were characterized from the morphological, structural, compositional, mechanical and microbiological points of view. Scanning electron microscopy revealed the presence, on top of the deposited layers, of spheroid particulates with sizes in the micron range. No micro-cracks or delaminations were observed. Energy dispersive x-ray spectroscopy and grazing incidence x-ray diffraction pointed to the existence of a C to Si compositional gradient from one end of the film to the other. Raman investigation revealed a relatively high sp 3 hybridization of up to 80% at 40–48 mm apart from the edge with higher C content. Si addition was demonstrated to significantly increase C:Si film bonding to the substrate, with values above the ISO threshold for coatings to be used in high-loading biomedical applications. Surface energy studies pointed to an increase in the hydrophilic character of the deposited structures along with Si content up to 52 mN m −1 . In certain cases, the Si-reinforced C coatings elicited an antimicrobial biofilm action. The presence of Si was proven to be benign to HEp-2 cells of human origin, without interfering with their cellular cycle. On this basis, reliable C:Si structures with good adherence to the substrate and high efficiency against microbial biofilms can be developed for implant coatings and other advanced medical devices.